Glossary Integration in Translation Classroom: EFL Pre-Service Teachers’ Perspectives - Hamida, Mimi; Basya, Dihliza; Ghozali, Imam (Universitas Dian Nuswantoro, 2024)
The purpose of the study was to investigate pre-service teachers' perceptions about the incorporation of the Glossary as serve a role in area of translation as a supporting tool that is used in translation efforts where they are used to clarify meaning in the translation classroom at one of the private universities in East Java. The researchers conducted a narrative inquiry using a qualitative approach. Three EFL pre-service teachers who had finished a translation course participated in semi-structured interviews to gather data for this study. The results of this study show that technical and non-technical complexity affect how the Glossary is used in the Translation class. Along with to the complexity, the research declares that participants saw a notable influence following active use of the Glossary. The information provided leads to the conclusion that any technological integration should be viewed from various angles, as demonstrated in this study in the pedagogical aspect in translation classrooms.